TRANSMISSION OF CULTURAL ELEMENTS IN TURKISH TEACHING TO FOREIGNS - Alpaslan OKUR (Fırat University, 2019)
Learning a foreign language means not only learning the structural use of a language, but also a meeting a new culture, being acquainted with that culture and finally adopting culture. The learners of a foreign associate their own culture with the one that learn via recognizing the people’s thought and attitudes in that new culture and they also make comparisons between them. As a result they get more tolerant viewpoints. The close relationship between language and culture reveals the fact that it is impossible to master a language without learning its culture. In the recent language teaching approaches among the transfer of culture has become important, the course book which are the essential part of classroom materials are based on culture of target language and reflect it. With the conscious selection of the text in the course book prepared to teach a foreign language, they might be highly efficient during learning process in terms of transfer of the culture. Regarding the idea that language teaching is an area of intercultural encounter, in this study the place and the significance of written texts which are among cultural transfer instruments and at the same time which have been used in Turkish as a foreign language courses are questioned, analyzed and culture transfer through textbooks has been evaluated following certain criteria within the context of teaching Turkish to foreigners based on İstanbul Turkish for foreigners series A1, A2, B1 and B2 course book. The evaluation of the İstanbul Turkish for foreigners course book series from the perspective of cultural transmission has revealed that they contain limited cultural elements in A1 and A2 levels course book, in B1 and B2 levels contains more cultural elements than A1 an A2 levels but they have to be enhanced more cultural elements.